2020
DOI: 10.3390/fi12110204
|View full text |Cite
|
Sign up to set email alerts
|

Digital Competence and Gender: Teachers in Training. A Case Study

Abstract: The ICTs are simultaneously an important tool and subject in teacher training. It, therefore, follows that digital competence is fundamental and constitutes a significant educational challenge, particularly the digital divide or gap by gender. The aim is to identify and analyze self-perceptions of digital skills, and the possible relationship of these to gender, in first-year university students taking a degree in primary education teacher training at a Spanish faculty of education. This is a descriptive study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 32 publications
3
17
2
1
Order By: Relevance
“…Contrary to previous studies [79], this study did not detect any gender gap in the students' digital skills, since both female and male students expressed relatively equal mean scores even in advanced digital skills like developing (DAM). These findings are encouraging for the future of the gender gap elimination in computing; however, further research should be conducted due to the current participants' characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to previous studies [79], this study did not detect any gender gap in the students' digital skills, since both female and male students expressed relatively equal mean scores even in advanced digital skills like developing (DAM). These findings are encouraging for the future of the gender gap elimination in computing; however, further research should be conducted due to the current participants' characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies in Europe have shown that gender can be a discriminating variable depending on the context and area of knowledge in which advanced training materials are used [41,42]. Gender gaps in self-concept about digital competencies in favor of males have also been identified when studying populations of university students [43]. However, in the geographic area analyzed in this study, these differences are almost completely diluted when differentiated by areas of knowledge or academic level.…”
Section: Discussionmentioning
confidence: 64%
“…and have a high online learning capacity (Grande- de-Prado et al, 2020;Senturk, 2020;Reimers & Schleicher, 2020). Teachers must overcome all the problems that occur in online learning and teaching (Aliyyah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%